2021
DOI: 10.3892/ol.2021.13156
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA‑103a‑3p could be a diagnostic and prognostic biomarker for breast cancer

Abstract: Breast cancer (BC) is the most frequent cancer for women worldwide. Recently, a spectrum of cell-free circulating microRNAs (miR) has been recognized as promising biomarkers for BC diagnosis and prognosis, among which miR-103a-3p has been reported in several types of human cancer. However, the role of miR-103a-3p in BC remains unknown. A total of 112 patients with BC and 59 healthy controls were recruited into the present study. The expression level of serum miR-103a-3p was evaluated using reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Recently, miR-875 and miR-103a-3p were described as potential prognostic markers in BC patients. Nonetheless, the number of evaluated patients was quite limited, in addition to the absence of a second validation cohort ( Liu H. et al, 2022 ; Liu et al, 2022 X. ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-875 and miR-103a-3p were described as potential prognostic markers in BC patients. Nonetheless, the number of evaluated patients was quite limited, in addition to the absence of a second validation cohort ( Liu H. et al, 2022 ; Liu et al, 2022 X. ).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of miR-329 in serum and tissue of patients with BC is associated with metastasis to lymph nodes while upregulation of miR-200 is correlated with metastasis to the brain, liver, and lung ( 84 ). Indeed, there are a number of studies that demonstrate the potency of certain miRNA utilization as BC biomarkers in various samples ( 56 , 86 93 ). Apparently, miRNAs maintain the healthy balance of signaling pathways for the normal function of the body.…”
Section: Diagnostic and Prognostic Function Of Mirnas In Breast Cancermentioning
confidence: 99%
“…miR-103a is suggested to be a biomarker for BC detection as its circulating levels are reported to be increased in patients with BC ( 86 , 210 ). Liu et al.…”
Section: Diagnostic and Prognostic Function Of Mirnas In Breast Cancermentioning
confidence: 99%
“…In addition to diagnosis, miRNAs have also been utilised as novel biomarkers in the prediction of prognosis (Zhang et al, 2019;Sun et al, 2019) and integrating multiple miRNAs might be more effective than single ones to predict prognosis (He et al, 2019). It is suggested that miR-103a-3p might be a potential non-invasive diagnostic and prognostic biomarker (Liu et al, 2022). Moreover, hsa-miR-584-5p detected as tumor suppressor miRNA is a potential candidate biomarker for coronary artery diseases (Coban et al 2020).…”
Section: Mirna-based Biomarkers For Diagnosis and Prognosismentioning
confidence: 99%